2012
DOI: 10.5812/jjm.4171
|View full text |Cite
|
Sign up to set email alerts
|

A Study of The Genetic Variability of Blastocystis hominis Isolates in Hamadan, West of Iran

Abstract: Blastocystis hominis is a common protozoan parasite in the human and many other animals intestine. the parasite pathogenicity is still controversial. A few studies have been conducted on prevalence of B.hominis subtypes in Iran. The results of present study improve our knowledge on B. hominis subtypes in Iran and therefore we can do more investigations on pathogenicity potential of these subtypes in the future. Background:Blastocystis is a common protozoan parasite in mammals, birds, amphibians, reptiles, fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…There has been less attention to B. hominis in the diagnostic and training field in Iran and clinicians do not believe in pathogenicity and its treatment that may play a role in increasing its prevalence. Result of only three genomic studies that were performed in Iran (36,60,64) are similar to many studies performed in other regions of the world that have reported ST3 as the most common subtype of B. hominis in the world (7% -92%) (78,79). Some researchers have attributed ST3 to urticaria, HIV and cancer (80).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…There has been less attention to B. hominis in the diagnostic and training field in Iran and clinicians do not believe in pathogenicity and its treatment that may play a role in increasing its prevalence. Result of only three genomic studies that were performed in Iran (36,60,64) are similar to many studies performed in other regions of the world that have reported ST3 as the most common subtype of B. hominis in the world (7% -92%) (78,79). Some researchers have attributed ST3 to urticaria, HIV and cancer (80).…”
Section: Resultssupporting
confidence: 74%
“…and limited to some specific areas in the country (36,60,64). We hope that similar investigations will be expanded in the future to collect more useful information to help health policy makers in this region to better understand the prevalence and pattern of the disease.…”
Section: Discussionmentioning
confidence: 99%